Metal-free intramolecular α-sp3 C–H oxygenation of tert-amine: An efficient approach to 1, 3-oxazines. Issue 49 (7th December 2016) - Deb, Mohit L.; Pegu, Choitanya Dev; Borpatra, Paran J.; Baruah, Pranjal K.
Graphical abstract: Highlights: Metal-free approach to 1, 3-oxazines via Cross-dehydrogenative coupling is reported. Shorter reaction time and high yield are the notable features of this method. Cheap and environmentally benign catalyst is used. The reaction could be scaled up and purified the product by recrystallization. Abstract: Here we disclose an iodine- tert -butylhydroperoxide promoted intramolecular sp 3 C–H oxygenation α- to tertiary amine for the synthesis of 1, 3-oxazines. The reaction is metal-free, atom economic, high yielding and proceeds within a short time under heating at 130 °C in DMF solvent. A variety of Betti bases of naphthol and phenol having cyclic as well as acyclic tert -amine moieties are employed as the starting materials. The Betti bases of naphthol produce single diastereomer of oxazine, whereas phenolic Betti bases give diastereomeric mixture. The mechanistic investigation suggests the non-radical pathway involving "I + " as the active catalytic species. The method gives excellent yield on multigram scale reaction.